The Role of AI in Academic Activities: A Comparative Analysis of Communication Dynamics in Jakarta and Perth - Yunus, Ulani; Ramonita, Latifa; Husada, Safaruddin; Allmark, Panizza (Jurnal Manajemen Teknologi, 2025)
Abstract.  This study explores how Artificial Intelligence has been adopted in communication at the higher education level by comparing institutions in Jakarta, Indonesia, and Perth, Australia. Grounded in Media Richness Theory and Cognitive Dissonance Theory, this study investigates how AI-based tools reshape communications practices, personalization of learning, and institutional adaptation in two divergent cultural and infrastructural contexts. The qualitative design involved collecting data through in-depth interviews with 32 participants —16 in each city —along with non-participant observations and document analysis of AI policies and institutional reports. All interview transcripts were thematically analyzed using NVivo 14 software, supported by Braun and Clarke's (2023) six-phase framework. Coding revealed four key themes: (1) AI as an administrative enabler, (2) pedagogical personalization and engagement, (3) cultural and ethical preparedness, and (4) institutional and policy alignment. Triangulating interview, observation, and document data further enhanced the credibility and depth of interpretation. For instance, results from Perth indicate a higher use of AI, with richer media interactions and greater readiness for institutional adaptation, compared to the fairly fragmentary, administratively inspired development of such use in Jakarta. The study adds to the theory by connecting communication richness and dissonance reduction mechanisms with specific AI adoption behaviors. It sets out some empirically based policy, training, and ethics governance recommendations for education.  Keywords: Artificial Intelligence; Academic Communication; NVivo; Thematic Analysis; Comparative Study; Jakarta and Perth